Review and Update of U.S. Coast Guard Vessel Stability Regulations and Guidance - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
U.S. Coast Guard (USCG) ship stability regulations governing the ability of a vessel to return to an upright position after being disturbed is the focus of a new TRB publication, Review and Update of U.S. Coast Guard Vessel Stability Regulations and Guidance. The authors advise the USCG on how it can make its stability regulations more usable and complete in meeting the requirements of different types of vessels and those vessels that have undergone weight changes that can affect their stability characteristics.The USCG has safety regulatory jurisdiction over vessels registered in the United States. One of its oldest regulatory functions is to ensure these ships, boats, and other floating vessels remain upright as they encounter both expected and unexpected loading, operating, and weather conditions, including wind and wave conditions and unexpected failure of watertight integrity.Stability standards have been improved over time - particularly in the past 30 years - and the USCG remains keenly interested in making sure the regulations are kept updated based on the latest technical knowledge, well aligned with international standards, and organized and presented in a manner that facilitates compliance and enforcement. The recommendations in the report are intended to further these aims. The USCG earlier commissioned a National Academies study to identify options for improving vessel stability regulations, and after receiving that study in September 2018, the USCG asked for this second study to provide more in-depth advice on applying these options.
Keywords: Transportation and Infrastructure

Toward New Naval Platforms: A Strategic View of the Future of Naval Engineering - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
The U.S. Navy has many unique naval engineering needs that demand a highly capable and robust U.S. naval engineering enterprise. In seeking an independent review of the unclassified elements of its National Naval Responsibilities—Naval Engineering (NNR-NE) program, the Office of Naval Research (ONR) asked for recommendations on ways to ensure the program meets the many naval engineering research, education, and workforce needs that will be critical to the Future Navy. Toward New Naval Platforms: A Strategic View of the Future of Naval Engineering recommends a number of strategies, including advice that ONR adopt a “lead, leverage, and monitor” framework for the programming, prioritization, and integration of its investments within and across the NNR-NE’s three “pillars” of science and technology (S&T), education and workforce development, and experimental infrastructure. The report points out that as the technological landscape critical to naval engineering continues to expand at a rapid pace, NNR-NE must make strategic choices about when it should invest directly in research that meets naval-unique S&T needs, and when it should leverage technological advances from other domains.Likewise, the report points to the importance of the NNR-NE making direct investments to inspire STEM interest among K-12 students and attract undergraduate and graduate students to the field of naval engineering but also to leverage the many STEM programs found elsewhere in the Navy and Department of Defense.The report stresses the importance of engaging individuals from under-represented groups to expand the naval engineering talent pool and to find creative ways to expedite the recruitment of workers to Navy-critical professions by providing naval engineering graduates with early work opportunities while awaiting security clearances.
Keywords: Transportation and Infrastructure

Revolving Funds for Sustainability Projects at Airports - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Airports continually balance demands to improve infrastructure within the realities of available budgets. Green revolving funds (GRFs) offer an alternative approach for investing in projects that generate operational savings. These funds work by tracking verified cost reductions from implemented actions, and then transferring those savings to a reserve that provides capital for future qualified projects such as energy system upgrades.A number of universities have managed GRFs for over a decade. Municipalities are starting to adopt them as well. ACRP Research Report 203: Revolving Funds for Sustainability Projects at Airports includes several non-airport-related case examples that have managed GRFs and two airport-related case examples. Airports require a modified GRF approach because of financial structures, Federal Aviation Administration (FAA) regulatory requirements, airline agreements, and the wide range of tenant roles.This ACRP report provides guidance to determine whether this innovative funding approach is suitable for a particular airport and instructions on how to deploy it. Airports that have the ability and determination to launch a GRF will gain a robust method for advancing their sustainability goals.
Keywords: Transportation and Infrastructure

Guide to Calculating Ownership and Operating Costs of Department of Transportation Vehicles and Equipment: An Accounting Perspective - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
A central role of a state Department of Transportation (DOT) fleet manager is to maintain a clear understanding of the fleet’s costs. This helps in tracking activities over time, comparing costs with other fleets, communicating with stakeholders, and effectively managing fleet assets.The TRB National Cooperative Highway Research Program's NCHRP Research Report 944: Guide to Calculating Ownership and Operating Costs of Department of Transportation Vehicles and Equipment: An Accounting Perspective provides a practical, logical, and transparent framework for conducting fleet cost accounting in state DOTs. The Guide focuses on the unique aspects of DOT fleets, although the principles in the Guide could be extended to any public fleet.Without a complete understanding of fleet costs, the fundamental functions of fleet managers—such as equipment replacement decisions, outsourcing decisions, and budget requests—are diminished. Ultimately, fleet managers need full confidence in their fleet cost numbers to have credibility with fleet stakeholders.The report is accompanied by a PowerPoint presentation summary.
Keywords: Transportation and Infrastructure

Renewing the National Commitment to the Interstate Highway System: A Foundation for the Future - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
TRB Special Report 329: Renewing the National Commitment to the Interstate Highway System: A Foundation for the Future explores pending and future federal investment and policy decisions concerning the federal Interstate Highway System. Congress asked the committee to make recommendations on the “features, standards, capacity needs, application of technologies, and intergovernmental roles to upgrade the Interstate System” and to advise on any changes in law and resources required to further the recommended actions. The report of the study committee suggests a path forward to meet the growing and shifting demands of the 21st century.The prospect of an aging and worn Interstate System that operates unreliably is concerning in the face of a vehicle fleet that continues to transform as the 21st century progresses and the vulnerabilities due to climate change place new demands on the country’s transportation infrastructure. Recent combined state and federal capital spending on the Interstates has been about $20–$25 billion per year. The estimates in this study suggest this level of spending is too low and that $45–$70 billion annually over the next 20 years will be needed to undertake the long-deferred rebuilding of pavements and bridges and to accommodate and manage growing user demand. This estimated investment is incomplete because it omits the spending that will be required to meet other challenges such as boosting the system’s resilience and expanding its geographic coverage.The committee recommends that Congress legislate an Interstate Highway System Renewal and Modernization Program (RAMP). This program should focus on reconstructing deteriorated pavements, including their foundations, and bridge infrastructure; adding physical capacity and operations and demand management capabilities where needed; and increasing the system’s resilience. The report explores ways to pay for this program, including lifting the ban on tolling of existing general-purpose Interstate highways and increasing the federal fuel tax to a level commensurate with the federal share of the required RAMP investment.View the videos, recorded webcast, graphics, summary booklet, press release, and highlights page at interstate.trb.org.
Keywords: Transportation and Infrastructure

Renewing the National Commitment to the Interstate Highway System: A Foundation for the Future: Japanese Version - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
TRB Special Report 329: Renewing the National Commitment to the Interstate Highway System: A Foundation for the Future explores pending and future federal investment and policy decisions concerning the federal Interstate Highway System. Congress asked the committee to make recommendations on the “features, standards, capacity needs, application of technologies, and intergovernmental roles to upgrade the Interstate System” and to advise on any changes in law and resources required to further the recommended actions. The report of the study committee suggests a path forward to meet the growing and shifting demands of the 21st century. The prospect of an aging and worn Interstate System that operates unreliably is concerning in the face of a vehicle fleet that continues to transform as the 21st century progresses and the vulnerabilities due to climate change place new demands on the country’s transportation infrastructure. Recent combined state and federal capital spending on the Interstates has been about $20–$25 billion per year. The estimates in this study suggest this level of spending is too low and that $45–$70 billion annually over the next 20 years will be needed to undertake the long-deferred rebuilding of pavements and bridges and to accommodate and manage growing user demand. This estimated investment is incomplete because it omits the spending that will be required to meet other challenges such as boosting the system’s resilience and expanding its geographic coverage. The committee recommends that Congress legislate an Interstate Highway System Renewal and Modernization Program (RAMP). This program should focus on reconstructing deteriorated pavements, including their foundations, and bridge infrastructure; adding physical capacity and operations and demand management capabilities where needed; and increasing the system’s resilience. The report explores ways to pay for this program, including lifting the ban on tolling of existing general-purpose Interstate highways and increasing the federal fuel tax to a level commensurate with the federal share of the required RAMP investment. View the videos, recorded webcast, graphics, summary booklet, press release, and highlights page at interstate.trb.org.
Keywords: Transportation and Infrastructure

Compendium of Successful Practices, Strategies, and Resources in the U.S. DOT Disadvantaged Business Enterprise Program - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Firms that have graduated from the federal Disadvantaged Business Enterprise (DBE) program or have successfully competed for state transportation agency contracts are the focus in NCHRP Research Report 913: Compendium of Successful Practices, Strategies, and Resources in the U.S. DOT Disadvantaged Business Enterprise Program.The DBE program provides small businesses owned and controlled by socially and economically disadvantaged persons with opportunities to participate on federally assisted highway contracts. As a requirement of receiving federal highway funds, state departments of transportation (DOTs) must administer the DBE program. FHWA provides oversight of the state DOTs’ operation of the program to ensure that they are in compliance with federal regulations.The report includes appendices that define success, profile successful DBEs, and describe state DOT initiatives for DBE success. It also explores the types of business assistance that contribute to the success of DBE firms.The report serves as a resource for staff in state transportation agencies, U.S. DOT, and other groups implementing the DBE program or providing business assistance.
Keywords: Transportation and Infrastructure

Challenges to Implementing Successful Land Use Strategies at Airports - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
TRB’s Conference Proceedings on the Web 24: Challenges to Implementing Successful Land Use Strategies at Airports is a compilation of the presentations and a summary of the ensuing discussions at an ACRP Insight Event held April 10-11, 2018, in Washington, D.C.The event brought together airport representatives and community planners to discuss effective strategies for improving their ability to partner on land use issues in the vicinity of airports.ACRP Insight Events convene airport industry leaders and subject matter experts in various fields to encourage discussion and promote broader and deeper insight on topics of significance to airport operators. These in-depth, face-to-face gatherings are designed to promote communication and collaboration, foster innovation, and help identify areas of future interest and research, especially for topics of emerging importance.
Keywords: Transportation and Infrastructure

Economic and Social Sustainability at Airports - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
TRB’s Airport Cooperative Research Program (ACRP) Conference Proceedings on the Web 23: Economic and Social Sustainability at Airports is a compilation of the presentations and a summary of the ensuing discussions at May 7-8, 2018, forum in Washington, D.C.The meeting brought together individuals from airports, airlines, academia, consulting, local and regional government, general sustainability professionals, and others. The forum included sessions on social sustainability, economic sustainability, keynotes on mitigating human trafficking and innovative development at airports, and interactive breakout discussions delving into myriad social and economic sustainability topics.ACRP organized the event as part of its series of convening activities titled “ACRP Insight Events.” ACRP Insight Events are forums that foster dialogue among professionals across sectors, institutions, and industries.ACRP Insight Events convene airport industry leaders and subject matter experts in various fields to encourage discussion and promote broader and deeper insight on topics of significance to airport operators. These in-depth, face-to-face gatherings are designed to promote communication and collaboration, foster innovation, and help identify areas of future interest and research, especially for topics of emerging importance.Copies of the slides of presentations made at the form are available online. The literature review prepared for the event is also available online.
Keywords: Transportation and Infrastructure

Economic and Social Sustainability at Airports - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
TRB’s Airport Cooperative Research Program (ACRP) Conference Proceedings on the Web 23: Economic and Social Sustainability at Airports is a compilation of the presentations and a summary of the ensuing discussions at May 7-8, 2018, forum in Washington, D.C.The meeting brought together individuals from airports, airlines, academia, consulting, local and regional government, general sustainability professionals, and others. The forum included sessions on social sustainability, economic sustainability, keynotes on mitigating human trafficking and innovative development at airports, and interactive breakout discussions delving into myriad social and economic sustainability topics.ACRP organized the event as part of its series of convening activities titled “ACRP Insight Events.” ACRP Insight Events are forums that foster dialogue among professionals across sectors, institutions, and industries.ACRP Insight Events convene airport industry leaders and subject matter experts in various fields to encourage discussion and promote broader and deeper insight on topics of significance to airport operators. These in-depth, face-to-face gatherings are designed to promote communication and collaboration, foster innovation, and help identify areas of future interest and research, especially for topics of emerging importance.Copies of the slides of presentations made at the form are available online. The literature review prepared for the event is also available online.
Keywords: Transportation and Infrastructure

Guidelines to Improve the Quality of Element-Level Bridge Inspection Data - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
TRB’s National Cooperative Highway Research Program (NCHRP) Web-Only Document 259: Guidelines to Improve the Quality of Element-Level Bridge Inspection Data is intended to assist inspectors in identifying defects and assigning the appropriate condition state for bridge elements.To ensure the safety and serviceability of bridges, the guidelines include accuracy requirements designed to help promote consistency in the collection of element-level data for bridges on the National Highway System.The quality of element-level bridge inspection data is critical for effective bridge management and asset management practices. Therefore, the guidelines also include a methodology developed to verify the impact of different accuracy requirements on deterioration models.The American Association of State Highway and Transportation Officials’ Manual for Bridge Element Inspection includes elements of the guidelines in NCHRP Web-Only Document 259.
Keywords: Transportation and Infrastructure

Bridge Demolition Practices - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
TRB's National Cooperative Highway Research Program (NCHRP) Synthesis 536: Bridge Demolition Practices documents practices used by bridge owners to manage and administer bridge demolition in construction projects.Each year hundreds of bridges are rebuilt or are entirely replaced as part of highway construction projects. Bridge reconstruction or replacement work often entails demolition of part or all of the bridge structure.Unintended events resulting in injury, project delays, and traffic disruptions can occur and have occurred during bridge demolition activities. The intention of this synthesis report is to assist in better understanding how to reduce risk associated with bridge demolition.
Keywords: Transportation and Infrastructure

Implementing the U.S. DOT Reasonable Modification Rule - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
TRB’s Transit Cooperative Research Program (TCRP) Synthesis 142: Implementing the U.S. DOT Reasonable Modification Rule provides an overview of the current state of practice regarding transit systems implementation of the U.S. Department of Transportation’s (DOT’s) Americans with Disabilities Act of 1990 (ADA) regulation 49 C.F.R Part 37.The report describes the experiences of agencies as they make reasonable modifications to their practices and policies in order to both respond to the regulation and ensure service to people with disabilities. The report also includes case examples of six transit systems, which present an in-depth analysis of the issues, opportunities, challenges, lessons learned, and keys to success in implementation of reasonable modifications . The need for future research is also discussed.Under the U.S. DOT regulations for implementing the ADA and Section 504 of the Rehabilitation Act of 1973 (49 C.F.R. Parts 37 and 27), transportation service providers and recipients of federal funding are required to ensure their services do not discriminate against people with disabilities.In 2015, the U.S. DOT amended 49 C.F.R. Parts 27 and 37 to require transportation entities to make “reasonable modifications/accommodations to policies, practices, and procedures to avoid discrimination and ensure that their programs are accessible to individuals with disabilities.” Effective July 13, 2015, 49 C.F.R. §37.169 of this final rule requires that public entity transit providers develop their own processes for making decisions and for providing reasonable modifications to their policies and practices.
Keywords: Transportation and Infrastructure

Emerging Technologies for Construction Delivery - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
The uses and levels of maturity of five advanced technology areas visualization and modeling, interconnected technologies, safety technologies, instrumentation and sensors, and unmanned aircraft systems in transportation highway construction projects are documented in TRB’s National Cooperative Highway Research Program (NCHRP) Synthesis 534: Emerging Technologies for Construction Delivery. The synthesis also investigates the implementation barriers and success factors for these technology areas and discusses the lessons learned as noted by state DOTs in their effort to study, test, and implement a new construction technology.As the highway construction industry infuses more technologies into the process of project delivery, state DOTs have an opportunity to realize improved project performance regarding cost, schedule, and quality.The Federal Highway Administration (FHWA) Every Day Counts (EDC) initiatives promote the use of various advanced and emerging technologies (e.g., automated machine guidance, unmanned aircraft systems, building information modeling, handheld instruments and devices, and work zone intrusion detection systems).
Keywords: Transportation and Infrastructure

Estimating the Value of Truck Travel Time Reliability - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Travel time reliability is frequently cited as an important metric for the trucking community and users of truck freight services. While the travel time reliability for trucking is commonly measured, truck reliability is seldom considered in the benefit–cost evaluation of mobility projects, which underrepresents the benefits accrued to freight users of the roadway system.The TRB National Cooperative Highway Research Program's NCHRP Research Report 925: Estimating the Value of Truck Travel Time Reliability provides planners and analysts a Reliability Valuation Framework that is applicable to urban or intercity shipments around the United States across a range of truck freight users and commodity types.
Keywords: Transportation and Infrastructure

Value, Benefits, and Limitations of Qualifications-Based Selection for Airport Project Delivery - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
About $1.5 trillion will be spent globally on airport infrastructure by 2030, according to the International Air Transport Association. Most of that enormous amount of money will be spent on projects that must be constructed without disrupting airport operations.Given the focus on schedule and on the cost of failing to complete the construction during the periods of planned outages, the need for a highly qualified construction contractor with a proven record of timely and quality production is key to the success of airport projects across the globe.The TRB Airport Cooperative Research Program's ACRP Synthesis 102: Value, Benefits, and Limitations of Qualifications-Based Selection for Airport Project Delivery aims to benchmark the state of the practice with respect to the use of qualifications-based selection (QBS) to award construction projects.
Keywords: Transportation and Infrastructure

Comprehensive Bus Network Redesigns - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
TCRP Synthesis 140: Comprehensive Bus Network Redesigns provides an overview of the current state of practice regarding comprehensive bus network redesign. The study examines practices among agencies of different sizes, geographic locations, and modes.The report captures the many components that are needed to successfully plan and implement a redesign and carefully considers the goals and objectives that agencies set forth when they began that process, helping them determine whether a redesign even made sense for the agency at that point in time.Comprehensive bus network redesigns, in which transit agencies fundamentally alter the structure and organization of their bus networks, are not completely novel in transit. However, redesigns have become seemingly more common in recent years. The motivations for embarking on network redesigns vary across transit agencies, but, given the prevalence of redesigns in recent history and with more redesigns likely to come, the transit industry will benefit from improved documentation of network redesign rationales, outcomes, best practices, and challenges.
Keywords: Transportation and Infrastructure

Practices on Acquiring Proprietary Data for Transportation Applications - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
TRB’s National Cooperative Highway Research Program (NCHRP) Synthesis 541 explores how state departments of transportation (DOTs) and metropolitan planning organizations (MPOs) acquire proprietary data for transportation applications.Recent technological advancements have led to new types of transportation data with characteristics that include improved quality and greater temporal and wider geographical coverage than traditional data sets. State DOTs and MPOs face challenges associated with obtaining new proprietary data.
Keywords: Transportation and Infrastructure

Promoting Aviation Career Education in High Schools and Community Colleges - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
More airport operations/management academic programs at both the high school and community college levels would help the airport industry. With baby boomers currently reaching retirement age at the rate of 10,000 each day, and later generations much smaller in size, new employees are not entering the workforce swiftly enough to replace those leaving because of retirement, illness, and other complicating factors.As a result, the aviation industry, like others, is experiencing a significant labor shortage. With no end in sight, the industry has joined forces in a number of unique partnerships in an effort to not only enhance the quality of current aviation graduates, but also stimulate interest in aviation careers among college students, high school students, and even middle school and elementary school students.The TRB Airport Cooperative Research Program's ACRP Synthesis 103: Promoting Aviation Career Education in High Schools and Community Colleges points out the many characteristics of high school and community college aviation programs throughout the country, which could prove useful to airport management. By better understanding the academic programs producing the next generation of aviation professionals, airports can develop proactive efforts to promote the airport profession to aviation programs in their local area and influence young people to seriously consider airports as a viable career path, thus positively affecting the future of the airport industry.
Keywords: Transportation and Infrastructure

Using Disaggregated Socioeconomic Data in Air Passenger Demand Studies - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
TRB’s Airport Cooperative Research Program (ACRP) Research Report: 194: Using Disaggregated Socioeconomic Data in Air Passenger Demand Studies explores the potential benefits of using disaggregated socioeconomic data, such as regional household income distributions and air passenger and travel survey data, for air passenger demand studies. Aviation demand is strongly correlated to socioeconomic activity, and analysts typically use aggregate socioeconomic data, such as gross regional product or average regional household income, to better understand current and potential future aviation demand. Since the United States is experiencing significant and ongoing demographic trends there is a question as to whether traditional methods and data sources will adequately capture these trends or would more detailed, disaggregated socioeconomic data, or even nontraditional data provide more accurate results. This report summarizes long-term socioeconomic trends, attempts to understand their potential impact, and provides guidance for incorporating disaggregated socioeconomic data into air passenger demand studies. The following appendices to ACRP Research Report 194 are available online: Appendix A: Detailed Survey of Past Analyses of Air Passenger Demand Appendix B: Airport Industry Use of Socioeconomic Data for Air Passenger Demand Studies Appendix C: Additional Material on Sources of Disaggregated Socioeconomic Data Appendix D: Detailed Case Study Analysis Results Appendix E: Background on Other Analytic Approaches
Keywords: Transportation and Infrastructure